Studies on Heavy Metal Accumulations in Green-Lipped Mussel Perna viridis from Malaysia by Using Multiple Linear Stepwise Regression Analysis - Yap, Chee Kong; Ismail, Abdul Rahim; Ismail, Ahmad; Tan, Soon Guan (Universiti Putra Malaysia Press, 2003)
The concentrations of Cd, Cu, Pb and Zn in soft tissue of green-lipped mussel Perna viridis from 15 sampling sites in Malaysia were found to be not serious but low when compared to regional data. However, samples from Kuala Perlis and Kg. Pasir Puteh should be given more attention since these locations were identified to have received anthropogenic metals. The multiple linear stepwise regression analysis was found to be useful in finding the most influential statistical parameters affecting heavy metal accumulation in P. viridis. The regression analyses indicated that the parameters were rather constant regardless of different sets of models being included in the procedure. Therefore, the multiple linear stepwise regression analysis can be proposed as an alternative statistical method for determining the most important variables affecting heavy metal accumulations in P. viridis as well as in other invertebrates.